2021
DOI: 10.1021/acsabm.1c00651
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Biointerface: Low-Temperature Surface Modification Strategies for Orthopedic Implants to Enhance Osteogenic and Antimicrobial Activity

Abstract: As both the average life expectancy and incidence of bone tissue reconstruction increases, development of load-bearing implantable materials that simultaneously enhance osseointegration while preventing postoperative infection is crucial. To address this need, significant research efforts have been dedicated to developing surface modification strategies for metallic load-bearing implants and scaffolds. Despite the abundance of strategies reported, many address only one factor, for example, surface chemistry or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The predominant primary bone sarcomas mainly include chondrosarcomas and osteosarcomas. Tumors that advanced cancers metastasizes to the bones are called secondary bone tumors 155 . Bone tumors possess a high tendency to disseminate to develop metastasis, characterized by leaky vasculatures, excessive growth, and hypoxic and acidic environment 156 .…”
Section: Application Of Gelma Hydrogel In Musculoskeletal Diseases Ge...mentioning
confidence: 99%
“…The predominant primary bone sarcomas mainly include chondrosarcomas and osteosarcomas. Tumors that advanced cancers metastasizes to the bones are called secondary bone tumors 155 . Bone tumors possess a high tendency to disseminate to develop metastasis, characterized by leaky vasculatures, excessive growth, and hypoxic and acidic environment 156 .…”
Section: Application Of Gelma Hydrogel In Musculoskeletal Diseases Ge...mentioning
confidence: 99%
“…125 In general, metallic materials are rapidly eroded by the impact of hostile biofluids and create toxic ions, affecting their biocompatibility. 126 One of the significant properties of biomaterials is the stability of the surface oxide layer. 127 Compared to other metal implants, the surface oxide stability of untreated stainless steel is relatively low.…”
Section: Wear Behaviors Of Stainless Steelmentioning
confidence: 99%
“…A recent review by Samyn [109] can be consulted for more detailed information and applications of several polysaccharides functionalized with polydopamine. Kim et al [110] indicated that coating application techniques and the durability of the mucoadhesive surfaces or coatings are as important as the functionalization techniques and should not be taken for granted. Table 4 compiled a list of works that utilized dopamine and its derivatives in mucoadhesion/mucus tissue applications, including polydopamine polymer.…”
Section: Abelmoschus Esculentus Inhibits Several Bacterial Film Growthmentioning
confidence: 99%